2018
DOI: 10.1038/s41419-018-1091-y
|View full text |Cite
|
Sign up to set email alerts
|

miR-3178 inhibits cell proliferation and metastasis by targeting Notch1 in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) has a poorer outcome than other subtypes of breast cancer, and the discovery of dysregulated microRNA (miRNA) and their role in tumor progression has provided a new avenue for elucidating the mechanism involved in TNBC. In this study, we identified that miR-3178 was significantly reduced in TNBC, and the low miR-3178 expression correlated with poor overall survival in TNBC but not in non-TNBC. The ectopic overexpression of miR-3178 suppressed TNBC cell proliferation, invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging studies have confirmed that different miRNAs play diverse roles in TNBC, some as tumorigenic agents, and some as tumor inhibitors. For example, as tumorigenic agents, miR-25, 16 miR-20, 17 miR-224, 18 miR-135 19 and miR-301 20 promote the occurrence and development of TNBC, whereas miR-124, 15 miR-4417, 21 miR-4306, 22 miR-199, 23 miR-1287 24 and miR-3178 25 as tumor inhibitors inhibit the oncogenesis and development of TNBC. In this study, relative miR-153 expression in TNBC tissues and cells was remarkably lower than that in corresponding adjacent noncancerous tissues and normal breast epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-8084, miR-708-3p, miR-96-182-183 cluster, miR-484, miR-210, and miR-142-3p modulate the invasive potential of BC cells by modulating EMT [16][17][18][19]. Recently, it has been shown that miR-124, miR-199a/214, miR-3178, miR-30a, miR-508-3p and miR-212-5p can modulate the level of EMT markers and TFs regulating the expression of E-cadherin in TNBC, a subtype that commonly metastasizes to the brain [51][52][53]85].…”
Section: Mirna-mediated Activation Of Emtmentioning
confidence: 99%
“…Angiogenic factors and growth factors either released by tumor cells or stromal cells individually or during their mutual crosstalk contribute to intravasation [89]. These factors allow tumor cells to invade through the basement membrane, adhere to the endothelial membrane, and pass through endothelial gap junctions to Table 1 miRNAs mediated regulation of BCBM miRNA Targets Regulation References EMT miR-8084 ING2, p53-BAX upregulated [16] miR-484 PAX-5 upregulated [19] miR-708-3p ZEB1, CDH2 and vimentin downregulated [17] miR-210 E-cadherin (ORF), PAX-5 upregulated [19] miR-142-3p Bach-1, CXCR4, MMP9, and VEGFR downregulated [18] miR-199a/214 Slug downregulated [51] miR-3178 Notch1 downregulated [52] miR-212-5p Prrx2 downregulated [53] miR-143 PUMA upregulated [35] miR-125a-5p ICAM-1 downregulated [38] miR-1258 HPSE downregulated [40] miR-210 Occludin, β-catenin upregulated [37] Cross Talk and Niche Formation miR-26a PTEN ATM upregulated [70,71] miR-19a PTEN upregulated [42] disseminate into the circulation [86]. Although no miRNA has been reported to influence intravasation directly, they can regulate angiogenic signals by targeting angiogenic factors and protein kinases.…”
Section: Mirna-mediated Intravasationmentioning
confidence: 99%
“…More targets regulated by miRNAs in TNBC have recently been revealed. Re‐expression of the silenced miRNAs miR‐17‐5p and miR‐3178 in TNBC inhibited cell proliferation and migration by targeting ETV1 and NOTCH1, respectively 34,35 . In addition, miR‐185 suppressed tumour proliferation by directly downregulating E2F6 and DNMT1, thus indirectly upregulating BRCA1 in TNBC 36 …”
Section: Micrornasmentioning
confidence: 99%